Hepatitis B virus (HBV) screening, linkage and retention-in-care in inclusion health populations: Evaluation of an outreach screening programme in London - Martyn, Emily (J Infect, 2024)
OBJECTIVES: We evaluate a hepatitis B virus (HBV) screening programme, delivered by a specialist pan-London multidisciplinary outreach team, to understand population characteristics and care cascade among people who experience extreme social exclusion (Inclusion Health (IH) groups). METHODS: Point-of-care HBV screening was performed in temporary accommodation for people experiencing homelessness (PEH) and people seeking asylum (initial accommodation centres, IACs) via a mobile unit staffed by peers with lived experience, nurses, and doctors. We analysed demographics and HBV characteristics of adults screened between May 2020 and January 2022. We ascertained linkage-to-care (LTC), retention-in-care (RIC) and loss-to-follow-up (LTFU). People LTFU were contacted by peers to re-engage in care. RESULTS: 2473 people were screened: 809 in IACs, 1664 in other temporary accommodation. Overall hepatitis B surface antigen (HBsAg) prevalence was 1.7% (43/2473), highest in IACs (3.5%, 28/809). LTC within 3 months was 56% (24/43) and RIC, 87% (26/30). LTC was higher when referred to a local IH-specialist hepatitis service, compared to other services (77%, 17/22 vs 33%, 7/21; p=0.006). LTFU was 30% (13/43), reduced to 21% (9/43) after intervention by peers. CONCLUSION: Our findings support outreach screening among IH populations and peer-supported linkage to IH-specialist hepatitis services. We recommend increased HBV testing and HBV-specific IH specialist services.